Integrative transcriptomic and metabolomic reveals squalene alleviating the inflammatory response and enhancing immunity of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) - Xiaobo Yan; Simiao Pan; Xiangxiang Suo; Weibin Huang; Tao Li; Shuang Zhang; Yuanzhi Yang; Beiping Tan; Xiaohui Dong (Aquaculture Reports)
Our previous study on plant oil substitution for fish oil found that corn oil induced inflammatory responses in grouper, while olive oil was effective in anti-inflammatory and immune enhancing. As a vital active ingredient in olive oil, squalene has been widely studied for its antioxidant and anti-inflammatory properties. Therefore, the present study was designed to use corn oil as the main lipid source to create a model of inflammation or low immunity and investigate the regulatory effect of squalene on the immunity of grouper, and to perform hepatic transcriptomic and metabolomic assays of grouper using omics technology, with the aim of providing basic data for the study of the mechanism of squalene. The results showed: squalene ingestion did not affect the growth performance of grouper (P > 0.05) but significantly improved immunity and the resistance of grouper to Vibrio harveyi (P < 0.05). Transcriptomic and metabolomic analyses showed that squalene activated the Wnt/β-Catenin signaling pathway and PI3K-Akt signaling pathway. Western blot results showed that squalene ingestion significantly upregulated Wnt/β-Catenin protein expression and downregulated the Axin protein expression (P < 0.05). Above results demonstrated that squalene enhanced immunity and disease resistance in grouper may be related to the activation of PI3K-Akt/ Wnt/β-Catenin signaling pathway, while the activation of β-Catenin could reduce the inflammatory response by inhibiting NF-κB-mediated inflammatory factors. The findings will contribute to the application of squalene as an immune enhancer for aquaculture and medical industry.